Участь Василя Доманицького в діяльності видавництва "Вік" - Цимбал, Б.В. (Слово і Час, 2019)
Статтю присвячено ранньому періоду діяльності київського видавництва “Вік” та участі в його роботі Василя Доманицького. Історію видавництва “Вік” до сьогодні належно не вивчено, тому автор зосереджується на трьох питаннях: 1) час заснування видавництва; 2) особовий склад співробітників; 3) участь Доманицького в його роботі. На основі детального аналізу наявних друкованих джерел та архівних матеріалів дослідник пропонує та обґрунтовує власну версію по кожному з порушених питань. The paper explores the initial activity of Kyiv publishing house “Vik” and Vasyl Domanytsky’s participation in its work. The history of the publishing house has not been properly studied yet. The vast majority of sources used by the scholars contain many inconsistencies, and the existing research works don’t pay attention to the causes of the differences, but rather exacerbate the problem due to uncritical attitude to the sources. The author, therefore, focuses on three issues: 1) the time when the publishing house was founded; 2) its employees; 3) Domanytskyi’s participation in its work. Researchers date the origins of the publishing house differently, within a wide period of 1894–1897. Most of them rely on a limited range of printed sources that may contain some mistakes. Based on the crossed analysis of the ‘main’ (popular) sources with the involvement of those less popular among specialists, the author identified the causes of differences in the works of the scholars and made an attempt to explain the causes of such inaccuracies. The new archival materials not only confirmed the results of studying the printed sources but also helped to establish the earliest documented date directly related to the work of the publishing house. This date may be reasonably taken as a starting point of its history. Studying the archival documents of the censorship department allows making some assumptions about the staff of the publishing house, which although remains insufficiently studied. The list of personalities is still limited to the five most famous members of the publishing circle. The findings also help to clarify the terminus post quem of Vasyl Domanytskyi’s involvement in the work of the publishing house. The results obtained are important not only for the further study of the history of Ukrainian book printing but also for highlighting the relationship of publishers with the censorship in the Russian Empire and the work of the Kyiv “Moloda Hromada” circle.